1983
DOI: 10.3109/08820138309025437
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism and Antibody Prodction in Immature Male Chickens

Abstract: This study was conducted to determine if hypothyroidism has an effect on humoral immunity in immature male chickens. Two week old Single Comb White Leghorn male chicks were used as experimental animals. Two experiments were conducted using different methods to induce hypothyroidism. In Experiment 1, birds were surgically thyroidectomized (Tx group) and in Experiment 2, hypothyroidism was induced by supplementing the feed throughout the experiment with 0.1% propylthiouracil (PTU group). Antibody production agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Thus, the enhanced total protein and globulin levels observed here could be caused by the antibodytype of proteins. It indicated that thyroid hormones have control over immunoregulation along with immune development as noted earlier (Yam et al, 1981;Mashaly et al, 1983). Similarly, the percent mortality was significantly less in both groups B and C when compared with the control in responses to A. hydrophila challenge.…”
Section: Discussionsupporting
confidence: 62%
“…Thus, the enhanced total protein and globulin levels observed here could be caused by the antibodytype of proteins. It indicated that thyroid hormones have control over immunoregulation along with immune development as noted earlier (Yam et al, 1981;Mashaly et al, 1983). Similarly, the percent mortality was significantly less in both groups B and C when compared with the control in responses to A. hydrophila challenge.…”
Section: Discussionsupporting
confidence: 62%
“…A few investigators have reported that reduced serum thyroid levels, due to the administration of goitrogens (chemical thyroidectomy), result in a decreased antibody response (Yam et al, 1981;Kai et al, 1988). Other studies have reported that thyroid hormone levels have little effect on antibody levels (Martin et al, 1988) and that somewhat suppressed serum concentrations of thyroid hormone may actually enhance the primary antibody response (Mashaly et al, 1983). This effect seems to be dependent upon the degree of thyroid inhibition, in that high dosages of propyl thiouracil (PTU), which effectively suppresses thyroid hormone concentrations, do seem to inhibit the antibody response (Kai et al, 1988).…”
Section: Thyroid Hormone Effectsmentioning
confidence: 95%
“…Yet there have been several reports indicating that measurable levels of thyroid hormones exist in the circulation of the surgically thyroidectomized (T x ) dog (Kallfelz, 1973;Li et al, 1986), rat (Taurog and Evans, 1967;Obregon et al, 1981), Japanese quail (Peczely et al, 1980), chicken (Harvey et al, 1983;Mashaly et al, 1983;Bachman and Mashaly, 1986;1987), and radiothyroidectomized chicken (Mellen and Wentworth, 1962). The half-life of T 4 and T 3 in chickens lies in the range of a few hours in length (Singh etal., 1967;May et al, 1974;Davison, 1978), which is shorter than the half-life of the hormones' counterparts in mammalian species.…”
Section: Introductionmentioning
confidence: 96%